Effects of delaying post‐hatch feeding on lipid peroxidation and antioxidant enzyme mRNA expression in the pectoralis major muscle of newly hatched chicks. (15th January 2020) - Kohrogi, Rukana; Shimamoto, Saki; Nakashima, Kazuki; Sonoda, Daichi; Ohtsuka, Akira; Ijiri, Daichi
Abstract: Excessive lipid peroxidation negatively affects the physiological response and meat quality of chickens. Delaying post‐hatch feeding was previously found to increase lipid peroxidation in the skeletal muscle of finishing broiler chickens. The aims of this study were to investigate the effects of delayed post‐hatch feeding on lipid peroxidation and the mRNA expressions of antioxidant enzymes in the pectoralis major muscle of broiler chicks during the post‐hatching period. Newly hatched chicks either had immediate free access to feed (freely‐fed chicks) or had no access to feed from 0 to 2 days old (delayed‐fed chicks), after which both groups were fed ad libitum until 4 or 13 days old. The lipid peroxidation level was higher in the delayed‐fed than freely‐fed chicks at 2, 4, and 13 days old. At 2 days old, the mRNA expressions of Cu/Zn‐SOD, Mn‐SOD, and GPX7 were lower in the delayed‐fed than freely‐fed chicks, while catalase mRNA levels did not differ. Furthermore, at 4 and 13 days old, lower mRNA expressions of Cu/Zn‐SOD and Mn‐SOD were observed in the delayed‐fed than freely‐fed chicks. These results suggest that delaying post‐hatch feeding reduces the mRNA levels of Cu/Zn‐SOD and Mn‐SOD, consequently affecting muscle lipid peroxidation in chicks during subsequent growth.